Dampak Kejadian Preeklamsia dalam Kehamilan Terhadap Pertumbuhan Janin Intrauterine - Hasliana Haslan; Ichsan Trisutrisno (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: The most common maternal death causes are bleeding, pregnancy hypertension (preeclampsia and eclampsia), and infections. Objective: Analyze the impact of preeclampsia in pregnancy on the growth of the fetus in the womb. Method: Observational analytical research with longitudinal panel study design. The population of pregnant women in samples taken by purposive sampling was 74 pregnant women. Results: Chi-square test P-value of 0.000 or <0.05, preeclampsia and OR 0.017 (0.002-0.15), and regression analysis of preeclampsia status had an effect of 0.017. The determinant coefficient (Negelkerke R Square) shows that the probability value of pregnant women experiencing preeclampsia can cause the possibility of fetal growth to be inhibited by as much as 48%. Conclusion: That preeclampsia dramatically affects the development of the intrauterine fetus. To improve the nutritional status of intrauterine mothers and fetuses, counselling can be done on pregnant women.